HUBUNGAN PENGETAHUAN KODE ETIK PROFESI PENATA ANESTESI DENGAN SIKAP MENJALANKAN PRAKTIK KLINIK DASAR DI RUMAH SAKIT MAHASISWA ANESTESIOLOGI UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Putra, Adek Khazelia; Listyaningrum, Tri Hapsari (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Background: A good knowledge of the professional code of ethics of anesthesiologists will help students deal with ethical problems that occur wisely and uphold ethical principles. Objective: This study aims to determine the relationship between knowledge of the professional code of ethics of anesthesiologists with the attitude of anesthesiology students of Universitas 'Aisyiyah Yogyakarta in carrying out basic clinical practice in hospitals. Method: This type of research is quantitative descriptive research using a cross-sectional research design. The sampling technique uses a simple random sampling technique of 58 respondents. Research Results: The results of the spearman rank test obtained a significance value (p-value) of 0.001 meaning smaller than < 0.05 and a contingency coefficient (r) value of 0.379. The majority of respondents have good knowledge of 53 respondents (75.7%) while respondents who have a good attitude in carrying out basic clinical practices in hospitals are as many as 50 respondents (71.4%). Conclusion: This study shows that there is a relationship between the level of knowledge of the professional code of ethics of anesthesiologists and the attitude of carrying out basic clinical practice in the anesthesiology nursing student hospital with a weak relationship and having a positive relationship direction.